Linkages analysis risk factors of the return process in logistics fast moving consumer goods - Evi Yuliawati; Clora Widya Brilliana (Universitas Serang Raya, 2022)
This study analyzed the linkage of risk factors in the return process of fast-moving consumer good (FMCG) logistics systems. The risk of returning products due to expired, near expiration, order errors and bad stock (damaged) haunts sustainable supply chains in the industry. In four business processes, warehousing, transport/distribution, production/supply and order processing identified twenty-two risk factors that cause the return process. The decision-making and trial evaluation laboratory (DEMATEL) method helps decision-makers simplify causal relationships between twenty-two complex risk factors. Through the depiction of the matrix and the network relationship map, twelve risk factors entered the dispatcher group, namely risk factors that can affect other risk factors that impact the return process on the FMCG logistics system. The result becomes a reference for decision makers to prioritize risk factors management that have a relationship with other risk factors, because the impact obtained will be maximal.